Determination of the Technical Rotation of Acacia nilotica Plantations for Production of Saw Logs and Associated Millable Wood Percentages (University of Khartoum Journal of Agricultural Sciences, 2025)
The objectives of this research were (i) to estimate thetechnical rotation of Acacia nilotica stands grown along the Blue Nile,Sudan, for the producion of saw logs that yield railway sleepers, and (ii)to estimate millable wood percentages at different crop ages for stands ofsite indices SI 25 and SI 28. The results revealed that mid-log diameters(over bark) of 36-47, 48-55, 56-64 and 65-68 cm were required toproduce single-, double-, triple- and tetra-sleeper logs, respectively. Thebest stands to produce saw logs for sleeper production were those of SI28 and SI 25, stands of SI 22 were marginal and those of SI 19 and SI 16were not suitable. The ranges of technical rotation were estimated as 25-36 years for stands of SI 22 to produce single-sleeper logs, 29-36 yearsfor stands of SI 25 and SI 28 to produce double and triple sleeper-logs,respectively. The results have important empirical implications inmanegerial decision making of A. nilotica plantations. Two curves ofpercentages of millable wood for total sawlogs and for sleeper logs alonewere constructed for stands of SI 28 and SI 25.
Keywords: Acacia nilotica; technical rotation; saw logs; millable wood